Increasing the Participation of Pregnant Women in Clinical Trials. Issue 3 (September 2019) - Heyrana, K.; Byers, H.M.; Stratton, P.
Abstract : ( JAMA . 2018;320:Number 20) Pregnant women are considered a "vulnerable" population in research and are often excluded from trials by institutional review boards and study investigators even when they may benefit from study interventions. This has led to >80% of pregnant patients routinely prescribed medications that have not been studied in pregnancy. It is mostly unknown which medications could cause harm, which interventions are effective, or whether treatment can safely be delayed until after pregnancy. The authors argue to improve the health of pregnant women and their fetuses, they need to be appropriately enrolled in clinical research so that decisions can be based on evidence-based medicine.